A contribuição do letramento visual em vídeos didáticos para o aprendizado de alunos surdos - Sordi, Aline (2022)
This research has the general objective of investigating, in educational didactic videos for the deaf, whether visual literacy is present and how it can contribute to the educational development of the deaf student, as well as presenting fundamental aspects that such materials should contain. The specific objectives were: a) to present the literacy strategies used by the teacher; b) point out in the videos aspects that should be taken into account when creating didactic videos for the deaf. This study had the contributions from authors such as (TAVEIRA, 2016; LEBEDEFF, 2010) who listed necessary aspects that didactic videos for the deaf should contain. Therefore, our object of study was the Sala 8 channel, on the YouTube platform, a channel created by a bilingual teacher and nominated for the Global Teacher Prize, “Nobel Prize” in Education, in 2020. Then, a selection of videos was made, categorizing them by disciplines, and presenting aspects listed as primordial in visual literacy. In total, eight videos were selected, presented as follows: Two of Mathematics, two of Portuguese, two of Science and two of Geography, with the purpose of identifying the strategies used and analyzing how they are marked by visual literacy. The analyzes were developed based on the concepts presented in the theoretical chapters. As a result, the quality and problematization of relevant aspects present in the videos stand out, emphasizing the need not only for linguistic, technological and visual knowledge in the production of videos for the deaf, but also for the context and for prior knowledge of deaf students. It is hoped, from this study, to contribute to the production of new didactic videos that train deaf students and that actually promote visual literacy. The analyzes were developed based on the concepts presented in the theoretical chapters. As a result, the quality and problematization of relevant aspects present in the videos stand out, emphasizing the need not only for linguistic, technological and visual knowledge in the production of videos for the deaf, but also for the context and for prior knowledge of deaf students. It is expected, from this study, to contribute to the production of new didactic videos suitable for deaf students and that in fact promote visual literacy.